Guihaia lancifolia (Arecaceae), a new species from Guangxi, China - Luo, Kaiwen; Xing, Fuwu; Tian, Jing (Phytotaxa, 2016)
Guihaia lancifolia K. W. Luo & F. W. Xing, a new species of Arecaceae from Guangxi Zhuang Autonomous Region, China, is described and illustrated. The new species clearly differs from Guihaia argyrata and Guihaia grossifibrosa in its long undivided leaf blades. Respectively, it is distinguished from Guihaia argyrata by glabrous sepals and ellipsoidal fruit, and has some differences from Guihaia grossifibrosa in the aspect of the erect and spine-like sheath fibers. Guihaia lancifolia is restricted to several karst limestone hills of central Guangxi, China.